Circulating adrenal 11-oxygenated androgens are associated with clinical outcome in endometrial cancer - Dahmani, Cylia; Caron, Patrick; Simonyan, David; Turcotte, Véronique; Grégoire, Jean; Plante, Marie; Guillemette, Chantal (Frontiers in Endocrinology, 2023)
Context Recent evidence support that androgens play an important role in the etiology of endometrial cancer (EC). Adrenal-derived 11-oxygenated androgens are highly potent agonists of the androgen receptor (AR), comparable to testosterone (T) and dihydrotestosterone (DHT) that have not been studied in the context of EC. Methodology We studied a cohort of 272 newly diagnosed postmenopausal EC cases undergoing surgical treatment. Circulating concentrations of seven 11-oxygenated androgens including precursors, potent androgens and their metabolites were established in serum samples collected before and 1 month after surgery using a validated liquid chromatography tandem mass spectrometry method (LC-MS/MS). Free (unconjugated) and total (free + sulfate and glucuronide conjugates following enzymatic hydrolysis) were analyzed in relation to clinicopathological features, recurrence and disease-free survival (DFS). Results Levels of 11-oxygenated androgens were weakly correlated to those of canonical androgens such as testosterone (T) and dihydrotestosterone (DHT), with no evidence of their association with clinicopathological features. Levels of 11-oxygenated androgens declined after surgery but remained higher in overweight and obese compared to normal weight cases. Higher levels of preoperative free 11-ketoandrosterone (11KAST) were associated with an increased risk of recurrence (Hazard ratio (HR) of 2.99 (95%CI=1.09-8.18); P=0.03). Postoperative free 11β-hydroxyandrosterone (11OHAST) levels were adversely associated with recurrence and DFS (HR = 3.23 (1.11-9.40); P=0.03 and 3.27 (1.34-8.00); P=0.009, respectively). Conclusion 11-oxygenated androgen metabolites emerge as potential prognostic markers of EC.